2007
DOI: 10.1111/j.1365-3059.2006.01560.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of five viruses infecting sweetpotatoes in Uganda; the first evidence of Sweet potato caulimo‐like virus in Africa

Abstract: In a survey of most sweetpotato-growing areas of Uganda, virus-like diseases were observed in all districts surveyed. Out of 338 fields sampled in 35 of the then 42 districts, 219 (65%) had some plants with symptoms. The most common symptoms included vein clearing, mottling, leaf distortion, yellowing, stunting and leaf strapping. Particularly high viruslike disease incidences (means of 34-86%) were encountered in districts around Lake Victoria and in the Rift Valley in southern and western parts of Uganda; pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 23 publications
6
44
1
Order By: Relevance
“…The SPCFV isolates used in this study originated from geographically distant regions of the world, including Uganda, Kenya, Tanzania, Peru, Taiwan, and China, or were of unknown geographic origin (Table 1). All SPCFV-infected samples from Uganda and some from Kenya were collected in the course of this study (5,6). Most isolates were subcultured every 2 to 3 months by sap inoculation to Nicotiana occidentalis subsp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPCFV isolates used in this study originated from geographically distant regions of the world, including Uganda, Kenya, Tanzania, Peru, Taiwan, and China, or were of unknown geographic origin (Table 1). All SPCFV-infected samples from Uganda and some from Kenya were collected in the course of this study (5,6). Most isolates were subcultured every 2 to 3 months by sap inoculation to Nicotiana occidentalis subsp.…”
Section: Methodsmentioning
confidence: 99%
“…Previous serological tests of sweet potato crops demonstrated that SPCFV has a wide geographic distribution, occurring in Brazil, Bolivia, China, Colombia, Cuba, Indonesia, Japan, Panama, Peru, Philippines (8,15,28), Kenya (6), Tanzania (29), and Uganda (5,24). In the three East African countries, SPCFV was the fourth most common virus, infecting about 5% (24) to 8% (5) of diseased plants in Uganda, about 3% of diseased plants in Kenya (6), and was rarely (just five plants) found in the Lake Zone of Tanzania (29).…”
mentioning
confidence: 99%
“…Despite this lack of data, farmers are unlikely to persist in growing crops which are so lacking resistance that very damaging proportions of plants are severely diseased, so resistant cultivars are normally grown where SPVD pressure is high (Bua et al ., ). In Kenya, the greatest disease incidence recorded in crops was 48% (Ateka et al ., ) and 86% in Uganda (Aritua et al ., ) but in both countries, some crops had little or no apparent disease. In two districts in Tanzania, incidences sometimes reached 100% but averaged only 17 and 33% (Ndunguru & Kapinga, ).…”
Section: Yield Losses Caused By Virusesmentioning
confidence: 97%
“…For example, virus infection inciting passion fruit woodiness disease showed a low incidence of up to 5% in eastern as compared to a high rate of 100% in central Uganda when 15 districts were surveyed (OchwoSsemakula et al, 2012). Also, cultivated sweetpotato showed low incidences of viruses and virus diseases in eastern region compared to central region in multiple surveys of up to 35 districts of Uganda (Aritua et al, 1998(Aritua et al, , 2007Mukasa et al, 2003). Cultivated sweetpotato cropping system in eastern Uganda is characterised by a break in two growing seasons as compared to central Uganda where the crop is continuously grown all year-round which explains low incidence in eastern versus high incidence in central (Mukasa et al, 2003).…”
Section: Several Viruses and Virus Diseases Infecting Cucur-bitaceousmentioning
confidence: 99%